Factors affecting response to National Early Warning Score (NEWS). (May 2015) - Kolic, Ivana; Crane, Smiley; McCartney, Suzanne; Perkins, Zane; Taylor, Alex
Abstract: Introduction: The NEWS is a physiological score, which prescribes an appropriate response for the deteriorating patient in need of urgent medical care. However, it has been suggested that compliance with early warning scoring systems for identifying patient deterioration may vary out of hours. We aimed to (1) assess the scoring accuracy and the adequacy of the prescribed clinical responses to NEWS and (2) assess whether responses were affected by time of day, day of week and score severity. Methods: We performed a prospective observational study of 370 adult patients admitted to an acute medical ward in a London District General Hospital. Patient characteristics, NEW score, time of day, day of week and clinical response data were collected for the first 24 h of admission. Patients with less than a 12 h hospital stay were excluded. We analysed data with univariate and multivariate logistic regression. Results: In 70 patients (18.9%) the NEW score was calculated incorrectly. There was a worsening of the clinical response with increasing NEW score. An appropriate clinical response to the NEWS was observed in 274 patients (74.1%). Patients admitted on the weekend were more likely to receive an inadequate response, compared to patients admitted during the week ( p < 0.0001). After adjusting for confounders, increasing NEWS score remained significantly associated with an inadequate clinical response. Furthermore, our results demonstrate a small increase in inadequate NEWS responses at night, however this was not clinically or statistically significant. Conclusion: The high rate of incorrectly calculated NEW scores has implications for the prescribed actions. Clinical response to NEWS score triggers is significantly worse at weekends, highlighting an important patient safety concern.